2009
DOI: 10.1088/1751-8113/42/28/285306
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement generation from deformed spin coherent states using a beam splitter

Abstract: Using the linear entropy as a measure of entanglement, we investigate the effect of a beam splitter on the Perelomov coherent states for the q-deformed Uq(su(2)) algebra. We distinguish two cases: in the classical q → 1 limit, we find that the states become Glauber coherent states as the spin tends to infinity; whereas for q ≠ 1, the states, contrary to the earlier case, become entangled as they pass through a beam splitter. The entanglement strongly depends on the q-deformation parameter and the amplitude Z o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Let us recall that in many applications one is interested in using highly quantum states (less classical) in order to be able to use, among other things, the entanglement of such states. In the previous works (see, for example, [33]), it was demonstrated that less classical states exhibit stronger entanglement. The results obtained can stimulate further studies and applications of the generalized su(1, 1) coherent states.…”
Section: Discussionmentioning
confidence: 97%
“…Let us recall that in many applications one is interested in using highly quantum states (less classical) in order to be able to use, among other things, the entanglement of such states. In the previous works (see, for example, [33]), it was demonstrated that less classical states exhibit stronger entanglement. The results obtained can stimulate further studies and applications of the generalized su(1, 1) coherent states.…”
Section: Discussionmentioning
confidence: 97%
“…It was recently shown by Ivan et al that if the input state to a beam splitter is a product state of the vacuum in one mode and a state with a sub-Poissonian distribution, then the output state will be entangled [23]. More recently, we have generalized this result to the states with super-Poissonian and sub-Poissonian statistics, by investigating the entanglement generated via a 50:50 beam splitter when a deformed spin coherent state is incident on one input port and a ground state is incident on the other [8]. We have distinguished two cases: in the classical q → 1 limit, the deformed spin coherent states go to Glauber coherent states in the limit of high spin, j → ∞, and thus become product states after beam splitter, whereas for q = 1, the states are entangled as they pass through a beam splitter and the entanglement is strongly dependent on the q-deformation parameter and the amplitude Z of the state.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, the characterization and the quantification of entanglement have attracted much attention and various entanglement measures have been proposed, such as linear entropy [8][9][10], concurrence [11][12][13][14], entanglement of formation [15] and negativity [16,17]. The fundamental problems regarding entanglement are to find a method to determine whether a given state of a composite quantum system consisting two or more subsystems is entangled or not and to choose the best measure quantifying the amount of entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…The study of coherent states for harmonic oscillator and other types of potentials has received great attention in literature, such as the coherent states for power-law potentials [23,24], Morse potential [25,26], pseudoharmonic oscillator [27], the coherent states with Kepler-Coulomb problem [20], and Pöschl-Teller potential and it's different forms [10,[28][29][30][31]. In this letter, we study the coherent states based on the definition given by Barut and Girardello of a space-like Pöschl-Teller potential which can be constructed by the temporal counterpart of the spatial Pöschl-Teller potential.…”
Section: Introductionmentioning
confidence: 99%